We already went through f(3/2) and f(b) with f(x) = x^2+2. I answered early this morning, and you said thank you 4 hours ago. Why are you asking for those again? You got f(3/2) correct then. Why are you now not sure?
At any rate, just substitute in the value wherever x appears.
f(-2) = (-2)^2 + 3 = 4+3 = 7
f(3/2) = (3/2)^2 + 3 = 9/4 + 3 = 5.25
f(b) = b^2+3
Not sure how you arrived at 9. It would help if you showed your work, so we can get an idea of where you are getting hung up.
If f(x) = x2 + 3, find the following.
f(-2) 9
f(3/2)== not sure
f(b) not sure
Thank you
1 answer